Levels, profiles, and distribution of perfluoroalkyl substances (PFASs) in groundwater in Bac Ninh province, Viet Nam - Thi Vi, Phung; Thuy Ngoc, Nguyen; Thanh Dam, Nguyen; Hung Viet, Pham; Hong Anh, Duong (Vietnam Journal of Science and Technology, 2025)
Paper-making is one of the potential sources of PFASs contamination in groundwater because the collection and treatment of sewage from paper-making activities have not been controlled effectively. For this reason, in this study, 12 PFASs in groundwater were analyzed during the dry season (n = 18) and the rainy season (n = 22) in Phong Khe (Bac Ninh), the largest paper-making village in Northern Vietnam. The results showed that the total PFAS concentrations ranged from non-detectable levels to 15.06 ng/L during the dry season and from non-detectable levels to 9.92 ng/L during the rainy season. Short-chain PFASs (C < 9) were more commonly detected in groundwater compared to long-chain PFASs. While perfluorohexane sulfonic acid (PFHxS) and perfluorooctanesulfonic acid (PFOS) were predominant in groundwater samples during the dry season, perfluorooctanoic acid (PFOA), perfluorohexanoic acid (PFHxA), and perfluoroheptanoic acid (PFHpA) contributed significantly to the composition of PFASs during the rainy season. Although these PFASs have not posed a health risk through groundwater consumption, future research is needed to investigate further the levels and distribution of these compounds in different environmental compartments within other potential craft villages.